The Road to Sèvres: Kurdish Elites and Question of Self-Determination After the First World War - Atmaca, Metin (International journal of conflict and violence, 2022)
This paper focuses on Kurdish elites and their quest for a Kurdish state during the Peace Conference that took place in Paris after the First World War. Cross-examining the British, French, Kurdish, and Ottoman sources, this paper shows that despite the failure to establish a Kurdish state in the aftermath of the disintegration of the Ottoman Empire the Kurdish elites, with their diplomatic and political experience and networking had equal, sometimes better, capacity to the leaders of other delegations in the Peace Conference. To demonstrate this, I focus on Kurdish elites, who were experienced in the imperial statecraft, especially Şerif Pasha, Sheikh Abdulkadir, Emin Ali Bedirhan, and Süreyya Bedirhan, lay out the complex relations amongst them and describe their efforts to represent the Kurds from the beginning of the Peace Conference until ratification of Treaty of Sèvres on 10 August 1920. In spite of what the available literature suggests, Kurdish elites, using all the available tools at their disposal, negotiated effectively for a Kurdish state. The contribution shows that the Kurdish elites not only presented a series of arguments during the Peace Conference but also laid down the basis for the Kurdish nationalism of the decades to come, with a historical narrative and a cartographic imaginary.